2013
DOI: 10.1364/ome.3.001075
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared supercontinuum generation in chalcogenides

et al.

Abstract: Davies B, "Experimental demonstration of linearly polarized 2-10 μm supercontinuum generation in a chalcogenide rib waveguide", Optics Letters 41, 5(2016) 958-961. Luther-Davies B, "High brightness 2.2-12 μm mid-infrared supercontinuum generation in a nontoxic chalcogenide step-index fiber", Journal of the American Ceramic Society, 99, 8 (2016) 2565-2568. 3.Madden S, "High Q factor chalcogenide ring resonators for cavityenhanced MIR spectroscopic sensing", Optics Express 23, 15 (2015)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
94
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(96 citation statements)
references
References 162 publications
0
94
0
2
Order By: Relevance
“…The SC spectra extending from the visible to 6 μm and from the visible to 4 μm were reported in tellurite glass using the pump pulses with central wavelengths of 1.6 μm [166] and 2.05 μm [167], respectively. A flat SC in the 2.5-7.5 μm range was produced in bulk chalcogenide glass using the pump pulse with a central wavelength of 5.3 μm [168]. The SC spectra with a remarkable mid-infrared coverage from 2.5 to ~11 μm were produced in As 2 S 3 and GeS 3 bulk chalcogenide glass samples using 65 fs pulses at 4.8 μm [169].…”
Section: ]mentioning
confidence: 99%
“…The SC spectra extending from the visible to 6 μm and from the visible to 4 μm were reported in tellurite glass using the pump pulses with central wavelengths of 1.6 μm [166] and 2.05 μm [167], respectively. A flat SC in the 2.5-7.5 μm range was produced in bulk chalcogenide glass using the pump pulse with a central wavelength of 5.3 μm [168]. The SC spectra with a remarkable mid-infrared coverage from 2.5 to ~11 μm were produced in As 2 S 3 and GeS 3 bulk chalcogenide glass samples using 65 fs pulses at 4.8 μm [169].…”
Section: ]mentioning
confidence: 99%
“…In a variety of waveguides, including silicon nitride waveguides [24] and chalcogenide waveguides [25] supercontinuum generation has been demonstrated. It can be shown that the widest supercontinuum spectra are generated when nonlinear waveguides are pumped at a wavelength were they have a small anomalous dispersion (for positive n 2 ) [20].…”
Section: Ultrashort Pulses In the Telecommunication Bandmentioning
confidence: 99%
“…Our group, in particular, recently reported spectral broadening spanning from 1.6 to 5.9 µm at -20 dB in an As 2 S 3 stepindex fiber driven by a 3.1 µm laser [213]. By using a longer driving wavelength 660 at 4 µm in a bulk chalcogenide glass a spectrum spanning from 2.5 µm to 7.5 µm could be demonstrated [214]. Simulations indicate that pumping an As-Se chalcogenide fiber at 4.5 µm could generate a spectrum from 3 µm to 12 µm wavelength [215].…”
mentioning
confidence: 94%